Information Security Behavioral Model: Towards Employees’ Knowledge and Attitude - Saurabh Mishra; Snehlata Snehlata; Anjali Srivastava (Universitas Islam Sultan Agung, 2014)
Information Security has become a significant concern for today’s organizations. The internal security threats acts as the most curtail type of security threat within an organization. These internal security threats are a result of poor conduct of security behavior by the employees within an organization. If not deal properly, it may hamper the auditing of organization. Auditing plays an important role in the business environment. Before conducting auditing it is essential to examine the behavioral aspect of the employees. The objective of this paper is to take out this internal threat that acts as a security slack, out of an organization by using a well-structured approach to develop a security behavior model. To validate the proposed model a survey method is used. The survey method measures the knowledge and attitude of an individual employee towards information security to analyze the behavioral security aspect of the employee’s. Statistical Analysis of the result of survey indicates that the employees’ knowledge and his attitude towards information security derive his behavior towards achieving ultimate organizational goal and thus validates the proposed security model.